Effect of jain fasting on anthropometric, clinical and biochemical parameters - Pratap Sanchetee; Prakash Sanchetee; M K Garg (Indian Journal of Endocrinology and Metabolism, 2020)
Background and Aims: Fasting has a long tradition in most cultures and has many health benefits. Most of the studies are from daytime fasting or intermittent fasting. There is paucity of data from complete fasting (no food and fruits, water only). This prospective study is conducted with aims to study impact of complete fasting on clinical and biochemical parameters. Methods: One hundred ten participants of either gender who voluntarily fasted (3-30 days) were included and underwent clinical and biochemical examination before and after fasting. Results: A total of 110 healthy volunteers (M: 27, F: 83) with mean age 51 ± 16 years (range 18-86) and body mass index 27.1 ± 4.9 kg/m2 (16.1-45.2) were studied. They had undergone fast for varying duration between 3-30 days (short fast: 3-7 days = 72; prolong fast: >7 days = 38). There were significant decrease in weight (66.8 ± 11.0 to 64.7 ± 11.1 kg, P < 0.0001), BMI (27.1 ± 4.9 to 26.2 ± 4.9 kg/m2, P < 0.0001), systolic blood pressure (130 ± 17 to 128 ± 15 mmHg, P = 0.012), serum globulin (3.10 ± 0.42 to 3.01 ± 0.41 mg/dl, P = 0.024), and serum high density lipoprotein (48.3 ± 12.2 to 45.7 ± 12.6 mg/dl, P < 0.0001) post fasting. However, significant increase was observed in pulse rate (81 ± 10 to 83 ± 11 beat/min, P = 0.001), fasting plasma glucose (102.9 ± 35.0 to 132.0 ± 42.0 mg/dl, P < 0.0001), serum triglycerides (137.6 ± 68.3 to 149.0 ± 67.1 mg/dl, P = 0.031), very low density lipoprotein (22.0 ± 10.5 to 24.2 ± 11.1 mg/dl, P = 0.010), and serum cortisol levels (13.5 ± 5.9 to 17.2 ± 6.3 μg/dl, P < 0.0001). These changes were more pronounced with prolong fasting, but were not affected by gender. Conclusions: Fasting results in improvement in anthropometric, physical and biochemical parameters related to physical health. It can be recommended as a mean for improving quality of life.